Evaluation of Rosuvastatin Effect as Adjuvant Therapy to Methotrexate on Lipid Profile and the Possibility of its Cardioprotective Effect in Iraqi Patients with Active Rheumatoid Arthritis - M. Mikhael, Ehab; A. Majeed, Ibrahim; I. Gorial, Faiq; H. Al-Ossamy, Mohammad; H. Falih, Ali; Abdulhameed, Dhikra (Iraqi Journal of Pharmaceutical Sciences, 2017)
Rheumatoid arthritis (RA) is a common inflammatory disease that associated with increased morbidity and mortality due to accelerated atherosclerosis. Rosuvastatin is a unique hydroxy methyl glutaryl Co A (HMGCoA) reductase inhibitor that has anti inflammatory effects.The aim of this study was to evaluate the effect of rosuvastatin as adjuvant therapy to methotrexate (MTX) on lipid profile and its possible cardioprotective effect in RA patients. A double blinded placebo controlled clinical trial with 8 weeks follow up periods at which 40 patients with active RA using MTX were randomized into 2 groups to receive either rosuvastatin 10mg or placebo as adjuvant therapy to MTX. In addition to twenty healthy subjects as control group. Lipid profile and erythrocyte sedimentation rate (ESR) was assessed at the start and at the end of the study. At the start of the study total cholesterol (TC), low density lipoprotein cholesterol (LDLc) and high density lipoprotein cholesterol (HDLc) values were not significantly different between RA patients and control group. At the end of the study rosuvastatin significantly reduced ESR, TC and LDLc after 8 weeks of treatment.It can be concluded that MTX has the ability to normalize lipid profile in RA patients. Rosuvastatin effectively reduce ESR, TC and LDLc; Moreover, Rosuvastatin might have a possible cardioprotective effect in RA patients.Keywords: Active rheumatoid arthritis, Methotrexate, Rosuvastatin.